Myths and Misconceptions about Communication Disorders: A Survey in North Karnataka region - K Sandhya; S Akshata; K N Meghana; N Sushmitha (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
Introduction: Communication disorders are highly prevalent in India especially in children. Early identification and treatment can prevent children from falling behind academically, socially, and in other key areas. However, identifying children with communication disorders and providing rehabilitation at an early stage is challenging in Indian scenario. Though 21st century has progressed drastically towards the rehabilitation of various communication disorders effectively, not all the regions in India are accepting the scientific rehabilitation. Due of lack of awareness, ignorance and stigma related to communication disorders, some open prejudices still persist in our country, making it difficult for people with communication disorders to have their condition recognized and to seek rehabilitation. However beforehand it is important to know the origin and degree of the problem so that appropriate remedy can be sought. Hence the present study makes one such effort, to study the extent of myths widely spread over north Karnataka region.  Method: A questionnaire consisting of 10 questions which focus on myths and misbelieves regarding communication disorders was administered on a total of Six hundred participants in the age range of 18 to 80 years.  Results: Results indicated presence of myths in rural population with respect to communication disorders compared to urban population as well as more misconceptions were noticed in older population when compared to younger ones.  Conclusion: From the results it can be concluded that further necessary programs needs to be implemented in rural areas and for older age groups of North Karnataka region to create awareness in this regard.